2012
DOI: 10.1111/j.1755-6724.2012.00711.x
|View full text |Cite
|
Sign up to set email alerts
|

Crustal Structure across the Northwestern Margin of South China Sea: Evidence for Magma‐poor Rifting from a Wide‐angle Seismic Profile

Abstract: We present results from a 484 km wide‐angle seismic profile acquired in the northwest part of the South China Sea (SCS) during OBS2006 cruise. The line that runs along a previously acquired multi‐channel seismic line (SO49–18) crosses the continental slope of the northern margin, the Northwest Subbasin (NWSB) of the South China Sea, the Zhongsha Massif and partly the oceanic basin of the South China Sea. Seismic sections recorded on 13 ocean‐bottom seismometers were used to identify refracted phases from the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…The location of the Mesozoic volcanic arc and the Mesozoic forearc basin identified in previous work (Li et al, 2018;Zhao et al, 2019) are shown in gray and yellow dotted line polygons, respectively. Seismic lines of OBS1993 (Yan et al, 2001), OBS2006-1 (Ding et al, 2012), OBS2006-3 (Wei et al, 2011), and OBS2010-1 (Cao et al, 2014) are shown in gray. White lines correspond to the magnetic lineations identified by Briais et al (1993).…”
Section: Seismic Experiments and Data Processingmentioning
confidence: 99%
“…The location of the Mesozoic volcanic arc and the Mesozoic forearc basin identified in previous work (Li et al, 2018;Zhao et al, 2019) are shown in gray and yellow dotted line polygons, respectively. Seismic lines of OBS1993 (Yan et al, 2001), OBS2006-1 (Ding et al, 2012), OBS2006-3 (Wei et al, 2011), and OBS2010-1 (Cao et al, 2014) are shown in gray. White lines correspond to the magnetic lineations identified by Briais et al (1993).…”
Section: Seismic Experiments and Data Processingmentioning
confidence: 99%
“…Magma‐poor margins include the conjugate Newfoundland, Canada, and Iberia Peninsula margins (e.g., Boillot et al, 1980; Shillington et al, 2006; Whitmarsh et al, 2001) and the Gulf of Aden (Autin et al, 2010; d'Acremont et al, 2005). Intermediate examples, with elements of both end‐members, include the South China Sea (e.g., Franke, 2013; Weiwei et al, 2012) and the Gulf of California (Lizarralde et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, existence of the HVL is still uncertain due to inadequate constraints from the refracted arrivals in the lower crust and lack of the reflections from top of the HVL. By far, studies on the crustal structures of the NW margin suggest an less prominent or absent HVL (Qiu et al 2001;Wu et al 2011;Ding et al 2012;Pichot et al 2014;Yu et al 2017;this work), as compared with the NE margin where a HVL with velocity of 7.3-7.5 km s -1 and thickness of several kilometres was detected along the OCT (Yan et al 2001;Wang et al 2006;Wei et al 2011). Distribution of the HVL may imply that the northern margin experienced different magmatic history laterally (Pichot et al 2014).…”
Section: Existing Seismic Studies Across the Nw Marginmentioning
confidence: 91%
“…A distinct high velocity layer (HVL) has been revealed at the bottom crust by refraction seismic surveys (Yan et al 2001;Wei et al 2011), restricted to slope areas in the NE margin. In comparison, existence of the HVL in the NW margin has long been controversial since wide-angle seismic modelling reported no such finding (Qiu et al 2001;Ding et al 2012;Wu et al 2011), while a few seismic surveys and gravity modelling revealed scattered thin HVL (Qiu et al 2013;Pichot et al 2014). The transverse discrepant crustal structures along the northern margin were suggested to be associated with the progressive continental rifting and opening of the SCS (Zhou et al 1995).…”
Section: Introductionmentioning
confidence: 99%